The follow-up of babies in the PMTCT programme in the West Rand - Makhanya, Faith Mathabo (My University, 2012)
Introduction Routine PMTCT programmes are highly effective in reducing the mother-to-child transmission (MTCT) rate of HIV, but generally fail in follow-up of HIV-exposed children. Loss to follow-up in the PMTCT programme translates into failure in primary prevention of new infections in HIV-exposed infants, failure to identify HIV disease early in children, and a missed opportunity for early referral of HIV-positive children to ARV sites. An assessment of what happens to babies born of HIV-positive mothers in the West Rand district of Gauteng province, South Africa has never been done, and neither has the extent to which these babies are followed up for the first 12 months, and the extent of loss to follow-up been documented. Aim The purpose of this study is to describe the referral and follow-up of babies born to HIV-positive women during July to December 2005 in the PMTCT programme in the West Rand district of Gauteng. Method This was a descriptive study involving a retrospective review of records for a cohort of babies born to HIV-positive mothers in the PMTCT programme in the West Rand during July 2005 to December 2005. All records of HIV-positive mothers seen over the six-month period at Leratong hospital and the two midwife obstetric units (MOUs) that refer patients to Leratong hospital were reviewed, as were records of their babies. A total of 887 Mother-infant pairs were consecutively enrolled in the study. Results Referral linkages within the PMTCT programme were found to be weak. Only 34% of babies enrolled in the PMTCT programme were successfully registered with PMTCT follow-up services. HIV PCR testing of babies enrolled in the PMTCT programme was relatively low. Overall only 41% of enrolled babies were tested for HIV infection. Of those babies who had a HIV PCR test, 16% were tested before or at six weeks with the majority of babies (84%) having a HIV PCR after six weeks. HIV PCR testing coverage at six weeks was 8.4%. Referral of confirmed HIV-positive babies to ARV sites was poor. Only 25% of all HIV PCR-positive infants were successfully referred to ARV sites. There was a high loss to follow-up in the PMTCT follow-up programme. The probability of an infant remaining in the PMTCT programme decreased from 0.5 at six weeks to 0.04 beyond 20 weeks. Conclusion Despite a high enrolment of babies in the PMTCT programme in the West Rand, referral linkages within the PMTCT programme are weak and there is a high loss to follow-up of infants in the PMTCT follow-up programme. HIV PCR coverage at six weeks is significantly low, and referral of confirmed HIV PCR-positive babies to ARV sites is also significantly low. Further research is needed to assess whether there has been an improvement in the follow-up of babies in the PMTCT programme in the West Rand since the time of this study.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Public Health. Johannesburg, April 2012
Keywords: HIV; Mother to child transmission